Cleopatra in space - Maihack, Mike (2014)
"When a young Cleopatra finds a mysterious tablet that zaps her to the far, REALLY far future, she learns of an ancient prophecy that says she is destined to save the galaxy from the tyrannical rule of the evil Xaius Octavian"--Publisher's web site
Vol. 1. Target practice -- . Vol. 2. The thief and the sword -- . Vol. 3. Secret of the time tablets -- . Vol. 4. The Golden Lion -- Vol. 5. Fallen empires
8-12
Reading Counts RC
Accelerated Reader AR
Keywords: Cleopatra, -- Queen of Egypt, -- -30 B.C. -- Comic books, strips, etc; Cleopatra, -- Queen of Egypt, -- -30 B.C. -- Juvenile fiction; Time travel -- Comic books, strips, etc; Time travel -- Juvenile fiction; Schools -- Comic books, strips, etc; Comic books, strips, etc; Fiction; Juvenile works; Science fiction comic books, strips, etc; Graphic novels; Graphic novels